EMI for International Class: How Do Students Perceive it? - Ira Maisarah; Irene Riskiana Vionauli Sinaga (Journal of English for Specific Purposes in Indonesia, 2024)
The internationalization of curriculum is an integration of the application of English as a Medium of Instruction (EMI) in recent years. This research aims to investigate the implications of internationalizing the curriculum through the implementation of English as Medium of Instructions (EMI) in international classes for Bengkulu University law students. The participants in this research were 2nd and 4th semester Law students who had joined the International class program with a total of 28 participants. This research uses a qualitative methodology design with the instruments used, namely a questionnaire using a Likert scale and interviews. The results show that students have positive perceptions and tendencies towards the application of EMI in international classes. However, there are several weaknesses and challenges faced, such as competency in language use and English proficiency certification. The implication is that the International Class Program as a means of implementing EMI in the learning process must follow international curriculum standards that are appropriate by paying attention to many aspects, including the abilities of students, teachers, stakeholders and program management. Therefore, in conclusion, the application of EMI has a positive effect and is highly recommended for all types of scientific disciplines by paying attention to international standard curriculum implementation standards.